Does Digital Entrepreneurship Education Matter for Students’ Digital Entrepreneurial Intentions? The Mediating Role of Entrepreneurial Alertness - Agus Wibowo; Bagus Shandy Narmaditya; Ari Saptono; Mohammad Sofwan Effendi; Saparuddin Mukhtar; Muhammad Hakimi Mohd Shafiai (Cogent Education, 2023)
AbstractDigital entrepreneurship is an interesting study in developed and developing countries as it plays a radical role in changing the economic landscape and facilitates creativity and innovation efforts for the growth of new entrepreneurs. This study aims to examine how digital entrepreneurship knowledge affects the digital entrepreneurial intentions of students. This research also explores the role of digital entrepreneurial alertness in mediating this relationship. We used a cross-sectional survey with a quantitative approach to convey the proposed hypotheses. A self-administrated survey of universities in Indonesia has participated in this survey. Later, the collected data were estimated using partial least squares structural equation modeling (PLS-SEM) with SmartPLS version 3.0. The results of this study indicate that digital entrepreneurial education and digital entrepreneurial knowledge can promote students’ digital entrepreneurial intentions. The findings also remark a significant effect of digital entrepreneurial alertness as a moderating variable for digital entrepreneurial education, digital entrepreneurial knowledge and students’ digital entrepreneurial intentions. This research provides insights linked to psychological dimensions in the form of digital entrepreneurial knowledge and digital entrepreneurial alertness as one of the predictor variables, as well as mediators for enhancing students’ digital entrepreneurial intention.